Lessons learned from isolated blunt major pancreatic injury: Surgical experience in one trauma centre. Issue 9 (September 2019) - Lin, Being-Chuan; Chen, Ray-Jade; Hwang, Tsann-Long
Highlights: Patients with IBMPI have longer injury-to-surgery times (median, 36.0 h), compared to those with multi-organ injury. Patients with blunt major pancreatic injury had high surgical complication rates, regardless of whether the injury was isolated or multi-organ. Patients with IBMPI who underwent distal pancreatectomy, the time interval from injury to surgery was a significant associated factor in preserving or sacrificing the spleen. Abstract: Introduction: The aim of this study was to present our surgical experience of isolated blunt major pancreatic injury (IBMPI), and to compare its characteristic outcomes with that of multi-organ injury. Materials and methods: From 1994–2015, 31 patients with IBMPI and 54 patients with multi-organ injury, who underwent surgery, were retrospectively studied. Results: Of the 31 patients with IBMPI, 22 were male and 9 were female. The median age was 30 years (interquartile range, 20–38). Twenty-one patients were classified as the American Association for the Surgery of Trauma–Organ Injury Scale Grade III, and 10 patients as Grade IV. Patients with IBMPI had significantly lower shock-at-triage rates, lower injury severity scores, longer injury-to-surgery time, and shorter length of hospital stay than those with multi-organ injury. There were no statistically significant differences in sex, age, trauma mechanism, laboratory data, surgical procedures, and complications between the two groups. Eight patients with IBMPI underwent endoscopic retrograde pancreatography, and 5 patients with complete major pancreatic duct (MPD) disruption underwent pancreatectomy eventually. The remaining 3 patients had partial MPD injury and two of them received a pancreatic duct stent for the treatment of existing postoperative pancreatic fistula. Spleen-sacrificing distal pancreatectomy (SSDP) was performed in 13 patient with IBMPI, followed by spleen-preserving distal pancreatectomy ( n = 12), peripancreatic drainage ( n = 4), and central pancreatectomy with Roux-en-Y reconstruction ( n = 2). The overall complication rates, related to the SSDP, SPDP, peripancreatic drainage, and central pancreatectomy, were 10/13 (77%), 4/12 (33%), 3/4 (75%), and 2/2 (100%), respectively. Three patients died resulting in a 10% mortality rate, and the other 16 patients developed intra-abdominal complications resulting in a 52% morbidity rate. In the subgroup analysis of the 25 patients who underwent distal pancreatectomy, SPDP was associated with a shorter injury-to-surgery time than SSDP. Conclusions: Patients with IBMPI have longer injury-to-surgery times, compared to those with multi-organ injury. Of the distal pancreatectomy patients, the time interval from injury to surgery was a significant associated factor in preserving or sacrificing the spleen.